Implementation of Loose Part Media-Assisted STEAM Learning Approach to Early Childhood Collaboration Skills - Pratiwi, Ni Komang Yadni Okta; Putu Rahayu Ujianti; Rendy Setyowahyudi (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
The problem in implementing STEAM learning is that teachers have difficulty integrating all STEAM elements into one activity or learning activity in the classroom. This research aims to analyze how the implementation of the STEAM learning approach with loose part media affects the collaboration skills of early childhood. This type of research is qualitative research, using qualitative descriptive methods and a case study approach. This research uses observation, interview and documentation data collection methods. The instruments used were observation sheets and interview sheets. The informant for this research was the group B teacher. Then, to validate the data, data analysis techniques were used in the form of triangulation, which consists of data reduction, data presentation, and drawing conclusions or verification. The results of this research indicate that the implementation of the STEAM learning approach assisted by loose part media in Kindergarten has been implemented well. Teachers have carried out learning activities through the stages of planning, implementation and evaluation. It is hoped that the implications of this research will be material for study and evaluation for teachers who will implement STEAM-based learning in kindergarten.